Effect of β-lactam antibiotics on the gut microbiota of term neonates - Hongdan Gu; Enfu Tao; Yijia Fan; Gao Long; Xinyi Jia; Tianming Yuan; Lihua Chen; Xiaoli Shu; Wei Zheng; Mizu Jiang (BMC, 2024)
Abstract β-Lactam antibiotics are a class of antibiotics commonly used to treat bacterial infections. However, the effects of β-lactam antibiotics on term neonatal intestinal flora have not been fully elucidated. Hospitalized full-term newborns receiving β-lactam antibiotics formed the antibiotic group (n = 67), while those without antibiotic treatment comprised the non-antibiotic group (n = 47). A healthy group included healthy full-term newborns (n = 16). Stool samples were collected for 16 S rDNA sequencing to analyze gut microbiota variations. Further investigation was carried out within the β-lactam antibiotic group, exploring the effects of antibiotic use on the newborns' gut microbiota in relation to the duration and type of antibiotic administration, delivery method, and feeding practices. The antibiotic group exhibited significant difference of microbial community composition compared to the other groups. Genera like Klebsiella, Enterococcus, Streptococcus, Alistipes, and Aeromonas were enriched, while Escherichia-Shigella, Clostridium sensu stricto 1, Bifidobacterium, and Parabacteroides were reduced. Klebsiella negatively correlated with Escherichia-Shigella, positively with Enterobacter, while Escherichia-Shigella negatively correlated with Enterococcus and Streptococcus. Regardless of neonatal age, β-lactam antibiotics induced an elevated abundance of Klebsiella and Enterococcus. The impact on gut microbiota varied with the duration and type of antibiotic (cefotaxime or ampicillin/sulbactam). Compared to vaginal delivery, cesarean delivery after β-lactam treatment heightened the abundance of Klebsiella, Enterobacteriaceae_Unclassified, Lactobacillales_Unclassified, and Pectobacterium. Feeding patterns minimally influenced β-lactam-induced alterations. In conclusion, β-lactam antibiotic treatment for neonatal pneumonia and sepsis markedly disrupted intestinal microbiota, favoring Klebsiella, Enterococcus, Streptococcus, Alistipes, and Aeromonas. The impact of β-lactam varied by duration, type, and delivery method, emphasizing heightened disruptions post-cesarean delivery.